A complete structural analysis of the FⅠ17 strike-slip fault and its hydrocarbon enrichment factors, Tarim basin, NW China - Chen, Shi; Liang, Xinxin; Song, Xingguo; Zhang, Yintao; Xie, Zhou; Neng, Yuan; Kang, Pengfei; Zhou, Jianxun (Frontiers in Earth Science, 2025)
The FⅠ17 fault is a prominent strike-slip fault in the central Tarim basin, notable for its hydrocarbon abundance and intricate tectonic attributes, characterized by several deflections in its planar trajectory. Analyzing the FⅠ17 fault offers crucial insights into the role of basement structures on the evolution and formation of intracratonic strike-slip fault systems. This study utilizes the latest seismic data and integrating the foundation of previous research to conduct a detailed investigation into the spatial distribution, deformation intensity, activity phases, and formation mechanisms of the fault. The fault can be divided into three structural layers based on deformation features. The deep layer, situated beneath the TЄ3 interface (the bottom of the Upper Cambrian), shows basement rifts and weak strike-slip activity. The middle layer, spanning from TЄ3 to TO3 (the bottom of the Upper Ordovician), exhibits pronounced deformation with flower-like structures. The upper layer, extending from the TO3 to TP (the bottom of the Permian), is marked by three groups of en-echelon normal faults. Controlled by Precambrian basement heterogeneity, the fault evolved through three stages: weak compressive stress during the Middle -Late Cambrian led to rupture along basement rifts and weak zones that formed the fault’s embryonic shape; strong compressive stress from Middle-Late Ordovician activated and propagated the fault upwards; during the Silurian-Carboniferous, the fault experienced episodic reactivation and result in the emergence of en-echelon normal faults. Hydrocarbon enrichment at the FⅠ17 fault is influenced by source rock distribution, reservoir characteristics, and fault reactivation. Its positioning above the source rock center ensures an ample supply of hydrocarbon. The intense fault activity has created favorable conditions for large-scale fracture-cavity reservoir development, and the reactivation period corresponds with the hydrocarbon accumulation phase, significantly boosts hydrocarbon charging.